OS08.4.A Analysis of melanoma brain metastasis immune microenvironment through multiplex gene expression profiling. (5th September 2022) - Ricci, A A; Collemi, G; Orlando, G; Tampieri, C; Senetta, R; Pellerino, A; Bruno, F; Melcarne, A; Garbossa, D; Rudà, R; Soffietti, R; Ribero, S; et al.
Abstract: Background: Novel immunotherapies based on targeting of specific immune checkpoints enabled a significant improvement of melanoma outcome, but melanoma brain metastases (BM) remain an unmet oncological need with an overall 2-year survival rate lower than 10%. Tumour immune microenvironment has been demonstrated to play a key role in BM establishment and development, but data regarding the specific milieu of melanoma BM is limited. Material and Methods: Gene expression profiles of 55 samples of primary melanoma and BM were evaluated using the nCounter PanCancer IO 360 Panel (NanoString Technologies) targeting 770 mRNA involved in tumor immune microenvironment modulation. The case series consisted of 10 primary melanomas and their 10 matched BM, 25 unmatched BM, and 10 locally advanced control melanomas without evidence of BM after >5 year follow up. Results: Among BM samples, most patients (25/45) were males and median age at BM diagnosis was 61, 2 years with a median time to BM development of 2, 1 years. Median OS from BM diagnosis was 1, 3 years. Several genes resulted significantly downregulated in BM compared to primary melanomas, including SERPINB5 (p<0.001), ARG1 (p=0.0067), S100A8 (p<0.001), S100A9 (p<0.001), S100A12 (p=0.0037), IL1RN (p=0.0012), CCL21 (p=0.0012), CCL22 (p=0.0012) and CCL13 (p=0.037) and SELE (p=0.026); conversely, C7 was upregulated (p<0.001). Downregulated signatures in BM involved those associated with multiple immune cell populations, including neutrophils, dendritic cells, mast cells and Treg, as well as inflammatory chemokines, the CTLA4 immune checkpoint and ARG1 enzyme function; conversely, MAGEs-related signature was upregulated. Comparison between primary melanomas which developed BM and those which did not showed a significant overexpression of RRM2 (p=0.0247) and TNFRSF1A (p=0.032) genes in the latter group and an upregulation of the PD-1 pathway. Analysis according to tumour mutational status showed an upregulation of signatures associated with inflammatory chemokines, dendritic and myeloid cells and neutrophils. No differences were observed according to time to BM development and survival from BM diagnosis. Conclusion: Our findings show that melanoma BM harbor distinct immunosuppressive mechanisms compared to primary tumors: this data elicits the importance of investigating the heterogeneity of BM microenvironment. Genes and pathways selectively overexpressed or downregulated in melanoma BM should be validated to be possibly considered as novel therapeutic targets.